The effectivenes of Audio Visual Media to Increase the Ability of the Student with Learning Dificulties to Recognize the Concept of Hundreds ( A Single Subject Research Conducted in Grade III of SDN 05 Kapalo Koto Pauh Padang) - REFITA OKTRIANI (Universitas Negeri Padang, 2016)
This reseacrhwas conducted at SDN 05 Kapalo Koto Pauh Padang. Based on the result of the previous observation, it was identifiled that a student with learning dificulties named X got problem in Mathematic learning. The student had not yet been able to recognize the concept of hundreds in which she could not mention the numbers correctly, could not write the numbers correctly and was not able to arrange them from the small one to the large one, and vise versa. To minimize the problem, audio visual media were applied. This was an experimental research which applied Single Subject Research (SSR) and A-B-A design.The result of the research indicated that after the intervention given, the ability of the student to recognize the concept of hundreds improved. The influence of audio visual media on the improvement of the student’s ability could be seen from the percentage of the data overlapped between the beseline 1 phase and the intervention phase (0%) and that between the intervention phase anf the baseline 2 phase (28,57%). The small percentage indicated that intervention exerted an influence upon the improvement of the student’s ability in recognizing the concept of hundreds. Therefore, audio visual media could be iused as a reference to cope with mathematic problem especially those related to the concept of hundreds. Thus, the use of audio visual media were affective to improve the ability of the student with learning difficulties to recognize the concept of hundreds in grade III of SDN 05 Kapalo Koto Pauh Padang. Keyword: audio visual media; concept of hundreds;learning difficulties